Quality of life long after temporal lobe epilepsy surgery. (10th March 2021) - Benevides, Maria L.; Costa Nunes, Jean; Guarnieri, Ricardo; Pauli, Carla; Wolf, Peter; Lunardi, Mariana; Kondageski, Charles; Neves Linhares, Marcelo; Lin, Katia; Walz, Roger
Abstract: Objectives: To identify variables independently associated with a meaningful improvement in QOL long after surgical treatment of drug‐resistant MTLE‐HS patients. Material & Methods: We prospectively evaluated 72 consecutive MTLE‐HS surgically treated patients and analyzed pre and post‐surgical variables independently associated with a meaningful improvement in QOL evaluated by the Quality of Life in Epilepsy‐31 (QOLIE‐31) overall score, and its domain scores determined at follow‐up after 36 to 131 months (mean 93 months) after surgery. Results: The mean overall QOLIE‐31 score and its subdomain scores improved significantly after surgery ( p < 0.01), and 55 patients (76.4%) had a meaningful QOL improvement. Being seizure‐free (Engel IA) after surgery showed a non‐significant association (OR 2.63, CI 95% 0.53 to 13.05, p = 0.23) and lower depressive symptoms a significant association (OR 4.15, CI 95% 1.19 to 14.53, p = 0.03) with meaningful improvement of QOL. Conclusions: Patients with MTLE‐HS who underwent epilepsy surgery show a sustained, meaningful improvement in their QOL. Pre‐surgical variables do not predict long‐term QOL improvement after surgery. Lower levels of depressive symptoms at postoperative evaluation are associated with meaningful QOL improvement.